Tradisi Masyarakat dalam Penanaman dan Pemanfaatan Tumbuhan Obat Lekat di Pekarangan - Sari, Ida Diana; Yuniar, Yuyun; Siahaan, Selma; Riswati, Riswati; Syaripuddin, Muhamad (Jurnal Kefarmasian Indonesia, 2015)
Home yard has been used to plant certain medicinal plants, also as known as TOGA program. This research was aimed to study the implementation of TOGA program and community tradition in planting and using medicinal plants. A qualitative research was conducted in West Java, Central Java, East Java and Bali which based on National Basic Health Research 2010 data had the highest percentage of jamu usage. Data was collected in 2011 through in depth interview and focus group discussion with related stakeholder and observation in research location. Result in Bogor district showed TOGA program has been included in Family Welfare Development Program and similar program was also developed in some villages. There was no certain TOGA program in Karanganyar, Sumenep and Gianyar districts. TOGA program in Karanganyar was inserted in other program due to economic needs while in Gianyar the program was originated from ornamental plants. The community usually used medicinal plants for the prime medication before going to health facility. Planting medicinal plants is an inherited tradition where parents become the main source of planting and usage information. The Agriculture Office and village officials had more significant roles to guide the community while the Health office only suggested or monitored them.